O impacto das placas neutras na produção de hidrogênio e oxigênio em um eletrolisador de água de compartimento único - KAROLINA FERRAZ FREITAS (2025)
The environmental crisis due to greenhouse gas emissions requires the exploration of alternative solutions for the energy transition. Thus, new palliative solutions are necessary to decrease the impact of the fossil fuel fed combustion engines currently operating. One alternative that still faces skepticism is combustion assistance by adding hydrogen. In fact, literature and commercial companies have increased the use and investigation of these electrolyzers due to the low cost, but there is still remaining question to be targeted, such as the role of neutral plates in one-compartment electrolyzers. This study investigates the impact of neutral plates on hydrogen and oxygen production in a one-compartment alkaline water electrolyzer equipped with stainless steel electrodes. Using NaHCO₃-based electrolytes, we analyzed the hydrogen and oxygen evolution reactions through half-cell and electrolyzer measurements. Various configurations with 3, 4, and 5 neutral plates were examined. Our findings reveal that reducing the number of neutral plates enhances current density and gas flow, indicating improved efficiency. Using electrochemical impedance spectroscopy, we found that the capacitors built by the neutral plates increase overall resistance, which can be used to control temperature. We also found the impact of the electrolyte conductivity on the performance of electrolyzers equipped with different neutral plates. Therefore, changing electrolyte may tune the conductivity, being a better strategy to control output current density, and temperature accordingly. We followed electrochemical parameters, flow of gases, and the composition of the output gases in long-time electrolysis, showing that it is possible to use low-cost one-compartment electrolyzers to stably produce hydrogen and oxygen in a virtually stable composition, which may be a solid alternative for the energy transition, regarding the optimization of liquid petrol gas and other fossil fuel combustion.